Generation and distribution of income in Mexico, 1990-2015 - Ayvar-Campos, Francisco Javier (2020)
Purpose: This paper aims to review the efficient use of economic and social resources to generate income and, at the same time, reduce the concentration of wealth in the 32 states of the Mexican Republic during the period 1990-2015. Design/methodology/approach: Data envelopment analysis with the inclusion of a bad output was used to diagnose the efficiency of Mexican entities, and the Malmquist–Luenberger index was applied to understand how this efficiency evolves. Findings:The results clearly show that only 3 of the 32 units studied generated and distributed wealth efficiently, while the other 29 must increase their level of income and its distribution. Originality/value: According to the authors’ knowledge, this is the first work that performs a temporal analysis of the efficiency in the generation of Human Development Index using bad outputs and the Malmquist–Luenberger index. Doi: https://doi.org/10.1108/JEFAS-04-2018-0040